2018
DOI: 10.21873/invivo.11429
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Thalidomide and Metronomic Chemotherapy for the Treatment of Canine Malignant Mammary Gland Neoplasms

Abstract: Background/Aim: The aim of the present study was to evaluate a multimodal approach for the treatment of canine malignant mammary gland neoplasms, including surgery, chemotherapy, thalidomide, and metronomic chemotherapy (MC). Materials and Methods: Fifty-eight female dogs were submitted to four different treatments: surgery; surgery with chemotherapy; surgery with chemotherapy and thalidomide; and surgery with chemotherapy and metronomic chemotherapy and overall survival was evaluated. Results: No statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Steady-state plasma concentrations ranging from 5 to 7 μg/mL resulted in stable disease for up to 74 weeks in 12/31 glioma patients, however, similar concentrations (6.2 μg/mL) for 8 weeks in metastatic breast cancer patients showed no tumour response [ 39 40 ]. In a recent study in dogs, a similar TAL dose to that reported in the present study, was associated with equal or even longer survival times compared to intensive-dose chemotherapy in splenic hemangiosarcoma and mammary carcinomas [ 18 20 ]. The average plasma concentration computed at the steady state at 11.7 mg/kg TAL administration once-daily in fed dogs resulted in 3.7 μg/mL.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Steady-state plasma concentrations ranging from 5 to 7 μg/mL resulted in stable disease for up to 74 weeks in 12/31 glioma patients, however, similar concentrations (6.2 μg/mL) for 8 weeks in metastatic breast cancer patients showed no tumour response [ 39 40 ]. In a recent study in dogs, a similar TAL dose to that reported in the present study, was associated with equal or even longer survival times compared to intensive-dose chemotherapy in splenic hemangiosarcoma and mammary carcinomas [ 18 20 ]. The average plasma concentration computed at the steady state at 11.7 mg/kg TAL administration once-daily in fed dogs resulted in 3.7 μg/mL.…”
Section: Discussionsupporting
confidence: 65%
“…The dose of TAL administered in the present study (400 mg/dog, average 11.7 mg/kg) was selected based on clinical efficacy/adverse effects previously reported in dogs. A dose of 8.7 mg/kg/day and a 3-month daily-dose of 20 mg/kg followed by a 3-month daily-dose of 10 mg/kg were successfully used in the management of stage II–III splenic hemangiosarcomas [ 18 ] and canine mammary carcinomas [ 20 ], respectively, in dogs. This latter study showed adverse sedative effects in some dogs when given the higher dose (20 mg/kg), with symptom improvement when the dose was reduced to 10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were classified as stage I–V [2]. Patients with at least stage III disease and at least tumor grade II received adjuvant chemotherapy with four cycles of 300 mg/m 2 carboplatin and 5 mg/kg of firocoxib every 24 h for six months according to the method of Bonolo et al [29]. Clinical follow-up was performed every three months in the first year with three-view thoracic radiographic examinations and complete blood counts.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were classified as stage I-V [2]. Patients with at least stage III disease and at least tumor grade II received adjuvant chemotherapy with four cycles of 300 mg/m 2 carboplatin and 5 mg/kg of firocoxib every 4 hours for six months Bonolo et al [29]. Clinical follow-up was performed every three months in the first year with three-view thoracic radiographic examinations and complete blood counts.…”
Section: Clinical Evaluationmentioning
confidence: 99%